2015
DOI: 10.1080/00218839.2016.1183934
|View full text |Cite
|
Sign up to set email alerts
|

Design of a food product composed of honey and propolis

Abstract: Propolis is a natural bee hive product with potential functional activities. Nowadays, many propolis products are available on the market, including cosmetics and food commodities. However, it is still unknown if edible products with propolis are fully accepted by consumers and are thus commercially viable, due to the bitter and resinous flavor and taste of propolis. This work is focused on the design of a "honey with propolis" foodstuff that can be welcomed by consumers, and, if possible, provide added benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…It is indicated that humans can consume 1.4 mg/kg body weight/day or approximately 70 mg/day as a safe dose (Burdock, 1998). Also, the study aimed at an acceptable amount of propolis in a designed food product with honey and propolis determined the suitable level as a maximum of 0.5% propolis content (Osés et al, 2015).…”
Section: Use Of Propolis In Foodsmentioning
confidence: 99%
“…It is indicated that humans can consume 1.4 mg/kg body weight/day or approximately 70 mg/day as a safe dose (Burdock, 1998). Also, the study aimed at an acceptable amount of propolis in a designed food product with honey and propolis determined the suitable level as a maximum of 0.5% propolis content (Osés et al, 2015).…”
Section: Use Of Propolis In Foodsmentioning
confidence: 99%
“…Some products containing propolis might have a strong flavor that affects their acceptability. Osés et al 7,31 studied honey samples with the addition of different proportions of propolis extracts and determined that products with more than 5 g soft propolis residue kg −1 were rejected owing to their unpleasant organoleptic characteristics. However, a sensory panel accepted all honeys with 1-5 g soft propolis residue kg −1 .…”
Section: Sensory Analysismentioning
confidence: 99%
“…A similar trend showing the increase in HMF concentration was reported for honey stored under different lighting conditions. 31 As HPGJ's water activity was 0.700, fungal growth could be a limiting factor in the product's shelf life. Al-Waili et al 39 investigated the antimicrobial activity of ethyl alcohol propolis extracts and their synergistic effect when used with honey.…”
Section: Storage Studiesmentioning
confidence: 99%
“…Other evidence establishes that honey enriched with propolis extract (0.3% and 0.5%, with 90% ethanol and 48 h of maceration) is promising, as it can maintain a good acceptance level in consumers. Furthermore, it showed a total phenolic compound and high flavonoids content (270.08 mg/100 g and 15.68 mg/100 g, respectively) compared to honey; however, the mixture with more than 0.5% of the extract was perceived as unpleasant, bitter, and intense [100].…”
Section: Enrichment Of Apiary Productsmentioning
confidence: 98%